Investigation of Anaerobic Power, Static Balance, and Speed Performances in 10-12 Years Old Children Doing or Not Doing Sports - TASKIN, Ali Kemal (Asian Journal of Education and Training, 2022)
In this study, it was aimed to investigate the anaerobic power, static balance, and speed performances of 10-12 years old children doing or not doing sports. In our study, 20 girls between the ages of 10 and 12 doing sports, and 20 girls between the ages of 10 and 12 not doing sports who both live in the city center of Batman voluntarily participated. The analysis of whether the data showed normal distribution was tested with the Shapiro-Wilk test, and the t-test was used to make comparisons between independent groups. At the end of the study, when the post-test results of the control and experimental groups were compared, a statistically significant difference was found in the vertical jump, standing long jump, static balance, and 100-meter sprint test values (p<0.05). There was no significant difference between the experimental and control groups in the 30 meter speed test values (p>0.05).